2018
DOI: 10.1093/ntr/nty255
|View full text |Cite
|
Sign up to set email alerts
|

Interventions Targeting Smoking Cessation for Patients With Chronic Pain: An Evidence Synthesis

Abstract: Introduction: Smoking is a risk factor for chronic pain conditions. Epidemiological evidence suggests that smoking cessation may be an important treatment target in people with chronic pain. The aim of this study was to examine the effectiveness of smoking cessation interventions in people with chronic pain. Methods: We systematically searched for clinical trials investigating the effectiveness of smoking cessation interventions for people with chronic pain, compared to any control comparator. Primary outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…Smokers experience more severe musculoskeletal and other chronic pain than nonsmokers because smoking causes tobacco-related diseases; damages musculoskeletal and other systems, leading for instance to osteoporosis, lumbar disc disease, and delayed bone and wound healing; and induces neuronal changes in pain pathways [ 11 ]. However, smoking cessation was not identified as an independent predictor of pain symptom changes in many studies [ 128 , 129 ]. Chronic pain patients who smoke often fail to experience pain relief when they stop smoking.…”
Section: Clinical Questionsmentioning
confidence: 99%
“…Smokers experience more severe musculoskeletal and other chronic pain than nonsmokers because smoking causes tobacco-related diseases; damages musculoskeletal and other systems, leading for instance to osteoporosis, lumbar disc disease, and delayed bone and wound healing; and induces neuronal changes in pain pathways [ 11 ]. However, smoking cessation was not identified as an independent predictor of pain symptom changes in many studies [ 128 , 129 ]. Chronic pain patients who smoke often fail to experience pain relief when they stop smoking.…”
Section: Clinical Questionsmentioning
confidence: 99%
“…Indeed, ongoing smoking becomes a risk factor for the onset or exacerbation of back pain, sciatica, arthritis, fibromyalgia, and chronic headache. [37][38][39][40][41] Nicotine (or perhaps another component in tobacco smoke) may sensitize pain receptors, decrease pain tolerance, and increase pain awareness. 42 Prospective cohort studies of adolescents bear this out, demonstrating that smoking early in life causes chronic back pain leading to related hospitalizations, initial opioid use, and potential opioid addiction persisting into adulthood.…”
Section: Biological Underpinningsmentioning
confidence: 99%
“…[43][44][45] Logically, it would follow that smoking cessation might then be a treatment for chronic pain, 34,46 but randomized controlled trials have not substantiated this hypothesis. 41 Continued research is needed to further elucidate the complex relationship between smoking and pain.…”
Section: Biological Underpinningsmentioning
confidence: 99%
“…There is evidence that smokers with pain (vs. no pain) are more likely to seek out pharmacotherapy for cessation (Zale & Ditre, 2014), and it has been suggested that these individuals may benefit from high-dose or combination nicotine replacement therapy (Hatsukami et al, 2007; Mills et al, 2012; Zale & Ditre, 2014). Behavioral cessation interventions have also been successfully administered to smokers with chronic pain (Saragiotto et al, 2018), and integrated treatments for pain and smoking have been shown to increase knowledge of pain-smoking interrelations, and confidence/intention to quit smoking (Ditre, LaRowe, Vanable, De Vita, & Zvolensky, 2019; Hooten, LaRowe, Zale, Ditre, & Warner, 2019).…”
Section: Discussionmentioning
confidence: 99%